Psychology of the Network Crowd as a Subject of Political Extremism - A. V. Zabarin (Управленческое консультирование)
The purpose of the article is to describe the psychological characteristics of the network crowd and their use to disseminate the ideology of political extremism, as well as to propose recommendations on countering these technologies. Opening the resources of foreign social networks for its citizens, Russia has become a hostage to unspoken rules. The problem with stopping the wave of extremist content demonstrates a serious threat to ensuring information sovereignty and emphasizes the relevance and significance of studying this problem. The methods of interdisciplinary theoretical analysis, synthesis, comparison, generalization and conceptualization of the scientific ideas of the use of the psychological effects of the crowd in the network space, the content of the analysis of the posts of participants in telegram channels during protest actions were used. The article develops an author’s approach to understanding the phenomenon of the network crowd as a specific hybrid that has arisen on the basis of social networks, embodying elements of an organized nucleus and spontaneous periphery. The idea of the mechanism of control of an organized network crowd as a function from the composition of the content to create emotional resonance, the activities of groups that disperse information on social networks and infection leaders, involving participants in social networks with their emotional response, is justified. Conclusions are drawn about the conditions under which the network crowd turns into a threat. Recommendations are proposed to counteract the indication of participants in social networks by the ideology of extremism.